KCNN2 mutation in autosomal‐dominant tremulous myoclonus‐dystonia. (3rd May 2020) - Balint, B.; Guerreiro, R.; Carmona, S.; Dehghani, N.; Latorre, A.; Cordivari, C.; Bhatia, K. P.; Bras, J.
Abstract : Background and purpose: Despite recent advances in neurogenetics that have facilitated the identification of a number of dystonia genes, many familial dystonia syndromes remain without known cause. The aim of the study was to identify the cause of autosomal dominant tremulous myoclonus‐dystonia in a UK kindred with affected individuals in three generations. Methods: Known genetic causes of myoclonus‐dystonia were excluded. We combined clinical and electrophysiological phenotyping with whole‐exome sequencing and Sanger sequencing to identify candidate causal variants in a family with tremulous myoclonus‐dystonia. Results: The core phenotype consisted of childhood‐onset dystonia predominantly affecting hands and neck, with a fast tremor with superimposed myoclonus and, in some individuals, subtle cerebellar signs. We identified a novel missense variant in potassium calcium‐activated channel subfamily N member 2 ( KCNN2 ) [NM_021614:c.1112G>A:p.(Gly371Glu)], which was the only variant that we were able to identify as segregating with the phenotype over three generations. This variant, which is absent from the most recent version of gnomAD, was predicted to be deleterious by SIFT and PolyPhen‐2 and had an overall CADD score of 29.7. Conclusions: KCNN2, a member of the KCNN family of potassium channel genes, is highly conserved across species and in humans is highly expressed in the brain, particularly the cerebellum. KCNN2 mutations have never been described as pathological in human disease, but are recognized abnormalities in two rodent models of fast, jerky tremor. Segregation, absence of the variant in the normal population and in‐silico prediction of a deleterious effect together with animal models compatible with the clinical phenotype are all in line with KCNN2 mutations being a plausible cause underlying myoclonus‐dystonia.